Communicating effectively in the workforce - Polack, Lisa (Aicpa Ser., 2020)
If you do not understand how communication works, then you may become perplexed and frustrated by interactions in the workplace. However, if you understand how communication works, then you have a good chance of diagnosing and fixing communication problems. Best of all, you can influence and motivate your employees, make better decisions, negotiate more effectively, build better work teams, and accomplish business objectives. This book discusses the various forms of communication.